Sobre o painel da pesquisa mensal de emprego (PME) do IBGE - Rafael Perez Ribas; Sergei Suarez Dillon Soares (Instituto de Pesquisa Econômica Aplicada (IPEA), 2008)
– The purpose of this article is to explain how to use the Pesquisa Mensal de Emprego (PME) and in particular to explain in detail how to set up the household panel. The PME household panel is an extremely useful analytical instrument that has been sadly underused due to several practical construction difficulties. The main objective of this text is to dispel these difficulties so as to open the household panel to researchers who previously did not know how to set it up. The first part of the text explains how to read the microdata and set up the PME household panel, and includes an explanation of its rotation scheme. Even this simple task becomes relatively complex due to how the PME is organized. The second part of the text deals with individuals and supplies some simple procedures for increasing the percentage of individuals successfully identified in the household panel. These procedures work because identifiable reporting error and identifiable changes in household composition reduce the percentage of individuals identified. Finally, we show how increasing the rate of individual identification improves econometric estimates using as an example labor market insertion.
Keywords: C23; C81; 330